2010
DOI: 10.1007/s10695-010-9418-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cadmium on some haematological and biochemical characteristics of Oreochromis niloticus (Linnaeus, 1758) dietary supplemented with tomato paste and vitamin E

Abstract: The present study investigates the potential protective effects of tomato paste (9 mg/kg-lycopene) in comparison with vitamin E (50 mg/kg) against the impacts of cadmium (Cd) toxicity (4.64 mg/l: ¼ of 96 h LC50) on fishes Cd exposed for 15 and 30 days. Cd impacts were evaluated in terms of biological, haematological and biochemical characteristics. Cd significantly induced free radicals in serum and liver. The activities of aspartate aminotransferase and alanine aminotransferase in serum were significantly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 83 publications
(71 reference statements)
16
38
0
Order By: Relevance
“…63,64 Our findings are in agreement with these tilapia sp. collected from wadi El-Rayan and Lake Qarun.…”
supporting
confidence: 89%
“…63,64 Our findings are in agreement with these tilapia sp. collected from wadi El-Rayan and Lake Qarun.…”
supporting
confidence: 89%
“…The present results showed that lycopene enhanced antioxidant capacity, thus protecting tissues against the DZN-induced damages, as shown by the maintenance of the TAO activity. These results suggest that vitamin E and lycopene have a protective effect on ROS as described in other studies (Mekkawy et al, 2011(Mekkawy et al, , 2013.…”
Section: Discussionsupporting
confidence: 86%
“…Diet supplementation with LYC and/or VE for 14 and 28 days showed improvement in behavioral changes and the fishes were noticed in better conditions. Similar results for vitamin E and lycopene were observed by Ohaida (2005), Mekkawy et al (2011Mekkawy et al ( , 2013, Soltan et al (2011) andUral (2013). Diazinon insecticides induce oxidative stress leading to generation of free radicals and alteration in antioxidant enzymes or oxygen free radicals scavenging enzyme (ElShenawy et al, 2010).…”
Section: Discussionsupporting
confidence: 70%
“…Blood glucose is a sensitive and reliable indicator of pollutants causing environmental stress in fish (Mekkawy et al, 2011). At the current study, fish exposed to acute and chronic concentrations of herbicide showed a significant increase (P<0.05) in serum glucose level during the exposure time than that of the control.…”
Section: Blood Biochemical Parametersmentioning
confidence: 51%